The Participation of Citizens in Garbage Waste Management in Tha - Sao Sub District Administration Organization, Krathum Baen District, Samut Sakhon Province - Wiseram , Nantaporn; Noppanatwongsakorn, Rachen (Dhammathas Academic Journal, 2020)
The objectives of this study: 1) were to study levels of citizens participation in garbage waste management of community in Tha-sao Subdistrict Administrative Organization, Krathum Baen District, Samut Sakhon Province, 2) were to study participation of citizens in garbage waste management of community in Tha-sao Subdistrict Administrative Organization, Krathum Baen District, Samut Sakhon Province. The research samples were 362 citizens live in Tha-sao Sub district Administrative Organization, Krathum Baen District, Samut Sakhon Province. This research used the stratified random sampling to find the sample groups. The research instruments used for data collection were the 5 point scale questionnaires with the discrimination index level of 0.20-0.80 and the reliability level of 0.87. The statistics used for data analysis were percentage, mean, standard deviation, t-test, and One-way analysis of variance, and Fisher’s method of multiple comparison tests. The research results found that: level in citizens participation in garbage waste management by separate each side is participation in decision, participation in operation, participation in has mutual benefit, and participation in evaluation. Which showed in overall that in high level, had average at 2.87 and the participation of citizens in garbage waste management of community, from the comparative study of split-sex, conclusion no different and the comparative study of split of age, education, occupation, income per month, numbers of years living in Tha-sao Sub district, found that collective participation were significantly different at the statistical level of .05.